Impactos da readaptação na constituição da identidade docente - Freitas, Marilce Ivama de (2021)
This study aims to understand the interference of readaptation in teacher´s identity, from the point of view of readapted teachers, who works in the Public Education Network in the City of São Paulo. For the development of this research, non-directive interviews were conducted with six readapted teachers, having Ciampa's Theory of Identity as the main theoretical basis. For the concepts´ building and the analysis of the contents presented by the teachers, other authors were also studied, such as Dubar (2003, 2005, 2009), Dejours (2007, 2015), Heloani (2004, 2015), Nóvoa (2007) and Placco and Souza (2015, 2016), among others. The literature review showed the presence of few studies on teacher readaptation and, therefore, the necessity to expand and to deepen the theme. The data from the “Portal da Transparência” (Transparency Portal) demonstrate the increase in cases of teacher´s readaptation, which, in the city of São Paulo, accounted for 9% of the total number of teachers, with the highest rate of readaptation being among teachers serving children and adolescents in the middle and high school. From the content presented in the six interviews, five axes were formulated: 1- How to start one´s narrative and professional choice, 2- Readaptation, 3- Work conditions and organization, 4- PPP (Political Pedagogical Project) and management team and 5- Sameness and metamorphosis processes, whose analysis enabled the perception that readaptation impacts on the constitution of the teacher´s identity, whose process will generate sameness and metamorphoses, according to the lived experiences, with the need for more attentive gazes and changes in directions to minimize the negative impacts